The Evaluation of Information Literacy among Medical Students at the College of Health Sciences, University of Ghana - Ankamah, S.; Gyesi, K.; Anaman, A.A. (Library Philosophy and Practice (e-journal), 2021)
The purpose of this study was to assess the information literacy of medical students at the University of Ghana. The convenience sampling technique was used to choose 206 respondents for the study, which yielded a response rate of 93.7 per cent. The study found that the majority of respondents needed information to acquire new knowledge in a subject area and to write assignments or project work. Moreover, most respondents rely on books, electronic books, and journals as their primary sources of knowledge. Furthermore, most respondents stated that they obtain their information via the internet. Additionally, most responders use the databases PubMed, ScienceDirect, and Google Scholar. Again, the majority of respondents are aware of the concept of plagiarism and will acknowledge the author of a book if they use a piece of it in their work or study. Last but not least, respondents’ major concerns about information access were low internet speed, high cost of books and other information materials, and information overload. Thus, it is strongly recommended among others that the CHS administration especially the CHS Library should manage and develop their collections in that required and relevant information sources will be available for students to use in their assignments and project works
Research Article
Keywords: information literacy; medical students; plagiarism; universities; University of Ghana